Validity of Therapeutic Agreements Between Doctors and Patients According to the Indonesian Civil Code - Desiana, Yacintha Yessica (PT FORMOSA CENDEKIA GLOBAL, 2023)
Humans are legal subjects who function as supporters of rights and obligations. Humans as social creatures have needs that can only be met if they have relationships with each other. The legal relationship between one party and another party creates an agreement that has reciprocal rights and obligations. An agreement or contract binds the parties who make it. Therefore, according to law, agreements are one source of engagement, in addition to various other sources. An agreement is also called an agreement, because the parties bound in an agreement agree to do something. Article 1313 of the Civil Code provides the following formulation of an agreement: